„Оповідання про царя Аггея" І. Франка в контексті зміни художніх парадигм - Московкіна, І.І. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2006)
В статье анализируется «Рассказ о царе Аггея» И. Франко в контексте изменений художественных парадигм рубежа столетий и делается вывод о том, что творчество писателя закладывало основы философской неомифологической прозы XX века. In the article was analyzed "Story About Tzar Aggey" by I. Franko in the context of transformations in aesthetic paradigms of the border of the centuries. It was concluded that Franko's works layed the foundations of philosophic new mythologic prose of the 20th century.
Keywords: Франко Іван; „Оповідання про царя Аггея"; передмодерн